Modal Sosial Kelompok Usaha Bersama Ibu-Ibu Kreatif Gerai Kembang Setaman Di Kelurahan Tirta Siak Kecamatan Payung Sesaki Kota Pekanbaru, Social Capital Of The Join Business Group Ibu-Ibu Kreatif Gerai Kembang Setaman In Kelurahan Tirta Siak Kecamatan Pay - Nadia Safitri; Rina Susanti (Peneliti.net, 2023)
The existence of social capital encourages the creation of group solidarity in order to achieve success and progress of the group. This study aims to determine the level of elements of social capital in the Joint Business Group of Ibu-ibu Kreatif Gerai Kembang Setaman and to analyze the strengths and weaknesses of social capital in the form of bonding social capital, bridging social capital and linking social capital in the Joint Business Group of Ibu-ibu Kreatif Gerai Kembang Setaman to maintaining the existence of the group. This study uses descriptive quantitative research methods with collecting data by observation, guided interviews, and documentation. The results of the study show the social capital in the Join Business Group of Ibu-ibu Kreatif Gerai Kembang Setaman is dominated by an element of trust. Next on bonding social capital and bridging social capital, elements of social capital, including networks, trust, and norms fall into the strong category. While the linking social capital in the Join Business Group of Ibu-ibu Kreatif that held by the members and business partner, the social capital element of trust and value is included in the strong category, but the social capital element of the network is included in the weak category.